Forensic patients’ experiences of Synthetic Cannabinoid Receptor Agonists (SCRAs) within custodial settings - Rogers, Gemma (The journal of forensic psychiatry & psychology, 2022)
There has been an enormous growth in New Psychoactive Substances (NPS), sometimes erroneously referred to as ‘legal highs’, over the past 15 years. There are currently at least 800 such compounds, and we lack adequate data on all their effects and harms. Synthetic cannabinoid receptor agonists (SCRAs), often referred to by the generic name ‘spice’, are particularly notable in this regard.There has been a lack of research on forensic patients’ experiences of SCRAs, their consumption, and any adverse impact they might have. This work qualitatively explored the experience of NPS and SCRA use in 19 male patients recruited from three secure forensic services in the South of England.The majority of participants discussed experiences of using SCRAs whilst in prison as opposed to their current forensic hospital admission. Three key themes emerged which describe participants experiences of SCRA use: (i) perpetuating cycle of drug use, mental ill-health, and crime; (ii) environmental injustices and consequences; and (iii) shame and stigma associated with SCRA use.The findings provide insights into the challenges faced by forensic patients as a result of SCRA use, as well as notable opportunities. A common call was for greater psychoeducation on drug harms and treatment opportunities.